Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Patricia, Patricia; Bangun, Primsa; Tarigan, Malem Ukur (Manajemen Bisnis Kompetensi, 2018)
This study aimed to examine the effect of profitability, liquidity, and firm size of the value of the company with financial performance as an intervening variable of manufacturing company listed on the Indonesia Stock Exchange (IDX) within period 2014-2016. The sample used is 58 companies. The results showed that profitability variable has significant positive effect on firm value, liquidity variable has insignificant negative effect on firm value, and firm size has no effect and positive on firm value. Profitability and liquidity has significant positive effect on financial performance, while firm size has no effect and positive on financial performance. The positive effect which are owned by profitability, liquidity, and firm size on firm value will be positive and strengthened when the performance of the company is increased.Keywords: profitability, liquidity, firm size, firm value, financial performance